AB0309 The impact of modern antirheumatic therapy on the neuropathic component of pain in patients with ra. (23rd January 2014) - Filatova, E.; Erdes, S.; Alekseev, V.
Abstract : Background: The main objective of Rheumatoid arthritis treatment is the achievement of permanent remission and suppression of symptoms of arthritis and extraarticular symptoms, prevention of destruction, dysfunction and deformation of joints, depression, risk of comorbidity, and improvement of the quality of life (1 ). For this purpose various drugs are used: non-steroidal anti-inflammatory drugs (NSAIDs), disease-modifying anti-rheumatic therapy (DMART), and more recently, biological therapy (BT). However, studies on the impact of modern antirheumatic therapy on the neuropathic pain (NP) component are scarce (2, 3 ). Objectives: Study the influence of modern antirheumatic therapy on the neuropathic component of chronic pain in RA. Methods: We recruited 183 patients (male:female ratio 1:10), aged 18-60 (average age 46±11.8 years old) admitted to the Research Center for Rheumatology. RA duration ranged from 3 months to 30 years (mean duration 9.03 ±7.6 years). All patients underwent rheumatological and neurological examination, identification and assessment of the neuropathic component using the DN4 questionnaire, and assessment of pain intensity during the study with the VAS scale. Mean duration of follow-up after treatment with NSAIDs, glucocorticosteroids (GC), DMART and BT was 3 weeks. Results: 78 patients (43%) with active RA presented with NP. Most of the 78 patients (76%) were taking NSAIDs, and 77% of patients were receiving DMART: methotrexate or sulfasalazine or Arava. 56% received systemic GC, 47% of them received intra-articular injections of diprospan. 16% of patients received BT. Since the treatment of patients with RA is complex, we have analyzed the dynamics of NP, disease activity and pain intensity depending on the mode of treatment. The patients were divided into three groups: I – 46 patients on NSAID + DMART treatment; group II included 20 patients who received NSAIDs + DMART and GC injections; III – 12 patients with BT infusion + DMART. The treatment was most effective in groups II and III. Conclusions: We postulate that the treatment affected primarily the nociceptive component of pain, the impact on NP was insufficient. The findings suggest that GC and BT have greater influence on NP in patients with RA. Therefore, for optimal control of chronic pain the use of combination treatment including anticonvulsants and antidepressants to address NP as recommended by EFNS may be recommended in some patients with RA. References: Ramos-Remus C., Duran-Barragan S., et al. «Beyond the joints. Neurulogical involvement in rheumatoid arthritis» Clin Rheumatol (2012) 31:1-12. Good AF, Christopher RP, Koepke GH, Bender LF, Tarter M (1965) Peripheral neuropathy associated with rheumatoid arthritis: a clinical and electrodiagnostic study of 70 consecutive rheumatoid arthritis patients. //Ann Intern Med 63:87–99. Agarwal V, Singh R, Wiclaf, Chauhan S et all. A clinical, electrophysiological, and pathological study of neuropathy in rheumatoid arthritis // Clin Rheumatol. 2008 Jul;27(7):841-4. Epub 2007 Dec 15. Disclosure of Interest: None Declared